The Existence of Collection in Muslim Philosophers’ Viewpoint (With Emphasis on Mulla Sadra and Ibn Sina) - v Khademzadeh; m Saeedi mehr (Metaphysics, 2010)
Concept of “collection” as a group of things that lack real composition and do not end in a new situation and configuration is one of the fundamental elements of some philosophical problems. So, the issue concerning the mode of existence of collection can make direct effect on different philosophical subjects. Some Muslim philosophers believe that the collection possesses a real existence and others consider it as an ideational entity. Most Muslim philosophers assume that numbers are real accidents of concrete things and this view seems to be dependent on their belief in the real existence of the collection. On the other hand, some parts of arguments for the impossibility of infinite regress such as the argument from collection and the argument from middle and side assume the real existence of the collection as one of their hidden premises. In this paper, after the exposition of the problem, views of the opponents of real existence of the collection and their arguments are examined. In the next step, the relation of Russell’s paradox and the mode of the existence of collection is explained. We conclude that acceptance of real existence for the collection has controversial results that make some expressions like “the collection of all existents” lack any reference.